Contribuição da logística reversa para a destinação de resíduos sólidos têxteis do APL do vestuário de Maringá/Cianorte - PR - Pinheiro, Eliane (2014)
The objective of this study was to identify the reverse logistics contribution to disposal of solid wastes from textile clothing APL Maringa / Cianorte - PR. Thus, the theoretical framework the following topics were discussed: reverse logistics, textile waste and Local Productive Arrangement. The method used in the research was deductive. The adopted methodological approach was applied research, qualitative-quantitative, exploratory and survey (survey). To collect data, we used a questionnaire divided into two blocks. The Block A consists of thirty-three items developed based on a theoretical framework. We used the Likert scale. This block aims to analyze the reverse logistics processes and include matters relating to the environment, costs and legislation. Block B covers the dimensions and characterization of textile waste from the APL, consist of five questions based on the National Inventory of Solid Waste. The study population consists of 32 industries, selected according to the criteria of accessibility. Data were tabulated, analyzed and treated through spreadsheets and Qualtrics tool. The theoretical framework based the discussion of the data. The results showed the reverse logistics processes used for the disposal of textile waste of APL, and these comply with the current legislation, but do not promote profit or advantages. The textile materials and wastes were sized and characterized. It is therefore necessary to implement control and separation of actions in order to promote proper disposal of these wastes aimed at valorising the same and consequently obtaining advantages and profits. Thus, it can be concluded that the proposed tool based on LR in sight as an instrument able to provide contributions to the APL of Maringa clothing / Cianorte - PR.